BS EN 6024. Aerospace series. Screws, 100° countersunk reduced head offset cruciform recess close tolerance shank, short thread in titanium alloy, anodized MoS2 lubricated. Classification: 1 100 MPa (at ambient temperature)/315°C. Inch series. (21st July 2021) - British Standards Institution,
No abstract available